Investigating the Role of Management Ownership in Revealing Firm Value - Deddy Mendai Zuhriansyah; Aprih Santoso (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
This study aims to analyze the role of management ownership in moderating the effect of total asset turnover on firm value. The data is taken from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. Using purposive sampling, 27 companies were selected as research samples. The data was processed by multiple regression analysis using the help of the IBM SPSS Statistic 25 application. The results showed that TATO had no significant effect on firm value. The results of testing the moderating variable show that management ownership does not moderate the effect of TATO on firm value Keywords: TATO, firm value, finance, ratio